From Curiosity to Active Engagement: The Teacher’s Role in Physics Learning - Suryati, Sri; Astalini, Astalini; Kurniawan, Dwi Agus (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze how teachers foster students' curiosity and engagement in physics learning by identifying effective pedagogical patterns that simultaneously support active participation and enhance students’ intrinsic motivation. Methodology: This study employed a qualitative approach using a Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines. Data were collected from Taylor & Francis, Springer, and MDPI databases. Purposive sampling selected 29 articles (1984–2025). Data were analyzed using thematic analysis with document extraction sheets. Main Findings: Teachers act as facilitators, motivators, and learning designers in fostering curiosity and engagement. Effective strategies include inquiry-based learning, project-based learning, contextual approaches, and open-ended exploration. These strategies enhance intrinsic motivation and support cognitive, emotional, and social engagement, while promoting deeper conceptual understanding, scientific character development, and sustained curiosity through inquiry, experimentation, and reflective dialogue. Novelty/Originality of this study: This study integrates student curiosity and engagement into a unified analytical framework in physics education, offering a perspective that has rarely been addressed in prior research. This PRISMA-based SLR provides a systematic synthesis of evidence and advances understanding of how adaptive and collaborative teaching practices foster scientific curiosity in contemporary learning contexts.